THE OBVIATION HIERARCHY AND MORPHO SYNTACTIC MARKEDNESS - Aissen, Judith (Linguistica Atlantica, 2001)
Numerous languages of the Americas display special syntax and/or morphology in clauses containing two 3rd person core arguments (and no 1st or 2nd person argument). Because the principles underlying these systems share important properties with the obviation systems of Algonquian languages, it is assumed here that they are all organized in terms of (abstract) OBVIATION. This paper develops some aspects of aformal account of obviation within the framework of Optimality Theory (OT), and provides one answer to the question, what is the role of hierarchies in grammar? The answer suggested here is that hierarchies (scales) are not themselves part of grammar, but they provide the raw material from which grammatical constraints are generated. Various aspects of the morphology and syntax of obviation systems are described here in terms of constraint subhierarchies which are derived from the OBVIATION SCALE alone, orfrom the alignment of the obviation scale with other relevant scales.